Gastroduodenal intussusception due to gastrointestinal stromal tumor. Issue 11 (12th September 2018) - De, Utpal; Basu, Srijan
Key Clinical Message: Gastric GIST should be kept in mind in patients with gastric outlet obstruction. Abstract : Gastric GIST should be kept in mind in patients with gastric outlet obstruction.